Identifying Opportunities to Strengthen Service Delivery for Hypertension in Tajikistan - World Bank Group (World Bank, Washington, DC, 2019)
Hypertension is a major driver of pre-mature death and disability in Tajikistan, a low-income country in Central Asia. The high burden of disease also results in significant health care expenditure and lost labour productivity. Therefore, there is an urgent need to strengthen service delivery systems through early detection of high blood pressure, prompt diagnosis, sustained treatment maintenance, and the attainment of blood pressure control. The Ministry of Health and Social Protection and the World Bank undertook implementation research to identify effective and context-appropriate solutions for improving hypertension services. The assessment used the cascade framework to describe drop-offs along the continuum of care, collected patient and health care provider perspectives on the causes of discontinuities, used routine data from participating facilities in a Bank-supported operation, and drew on the international literature on chronic care interventions. The report presents feasible and cost-effective recommendations that, if adopted, can strengthen current programs and policies to address the growing burden of hypertension in Tajikistan.